2007
DOI: 10.1007/s11664-007-0298-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of Gate Oxide in AlGaN/GaN High-Electron-Mobility Transistor pH Sensors

Abstract: We report on a comparison of different gate oxides for AlGaN/GaN highelectron-mobility transistor (HEMT) pH sensors. The HEMTs show a linear increase in drain-source current as the pH of the electrolyte solutions introduced to the gate region is decreased. Three different gate oxides were examined, namely the native oxide on the AlGaN surface, a UV-ozone-induced oxide and an Sc 2 O 3 gate deposited by molecular beam epitaxy. The Sc 2 O 3 produced superior results in terms of resolution in measuring small chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…For pH values above neutral, both GaN and AlGaN show decreasing I ds with increasing pH [18,20,31]. This is consistent with our results for both RTA oxidised GaN and RTA oxidised AlGaN surfaces which showed that exposure to NaOH/NaCl results in OH − formation (seen in Fig.…”
Section: Resultssupporting
confidence: 91%
“…For pH values above neutral, both GaN and AlGaN show decreasing I ds with increasing pH [18,20,31]. This is consistent with our results for both RTA oxidised GaN and RTA oxidised AlGaN surfaces which showed that exposure to NaOH/NaCl results in OH − formation (seen in Fig.…”
Section: Resultssupporting
confidence: 91%
“…The epi-layers were grown by Metal-Organic Chemical Vapor Deposition on Si substrates. The sheet carrier concentration was cm and the mobility was 980 cm /V-s at 300 K. For the pH sensing, 100 Å Sc O was deposited as a gate dielectric through a contact window of SiNx layer [22], [23]. Fig.…”
Section: Methodsmentioning
confidence: 99%
“…on GaN-based ISFETs were investigated and demonstrated [12,14,15]. A variety of methods are frequently to deposit metal-oxide membrane layers, such as sputtering, chemical vapor deposition, atomic layer deposition, and chemical wetness technique.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of methods are frequently to deposit metal-oxide membrane layers, such as sputtering, chemical vapor deposition, atomic layer deposition, and chemical wetness technique. [13][14][15][16]. However, the former three methods belonging to high-energy processes might damage the chemical composition and induce surface defects, which would cause the long-term instability and poor reliability of an ISFET [17].…”
Section: Introductionmentioning
confidence: 99%